GLOMOMIDIELLA N. GEN. (FORAMINIFERA, MILIOLATA, NEODISCIDAE): A NEW GENUS FROM THE LATE GUADALUPIAN-LOPINGIAN OF HYDRA ISLAND (GREECE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
A new genus of Foraminifera (Miliolata, Cornuspiroidea, Neodiscidae) is erected from the late Guadalupian (Capitanian = Midian) to Lopingian sedimentary succession of the island of Hydra (Greece). It represents an important phylogenetic form, probably at the origin of several genera (or subfamilies of the authors) that became relatively widespread during the Lopingian (Late Permian). Glomomidiella n. gen. is characterized by an entirely glomospiral coiling and rudimentary pseudoseptation.
Keywords: Middle Permian; Late Permian; Foraminifers; New taxa; Biostratigraphy; W Tethys